Meme virality and humour style: Exploring internet memes as a multimodal language in social media - Balan, Sunshine G.; Aguipo, Keith Daryl A.; Cabaguing, Ronalyn A.; Edar, Lynjel P.; Nacionales , Joseph P.; Claridad , Norberto (Journal of Language and Pragmatics Studies, 2023)
The study only includes the randomly chosen students from one of the state universities in Tacloban City, Philippines, in its scope. This study takes into account every aspect of the students' individual personal lives, including their understanding and prior experience with internet memes. For this study, the researchers used qualitative research, especially the survey/interview method. This design will be used by the researchers to examine the influence that an internet meme has on an individual across all social media platforms. Studies that use randomization and the evaluation of interventions are known as qualitative research. The following factors contributed to the researchers' decision to randomize the respondents: (1) easy access to study participants, (2) large/universal sample size, and (3) to be able to identify trustworthy participants who, based on their own experiences, have sufficient knowledge of internet memes. Memes can be used to spread a particular message, serve as a platform for mass communication, and serve as a form of entertainment, according to the study's analysis of data from 26 carefully chosen participants. According to the research, it would be preferable for the reader to understand the meme's meaning because it would make it possible for them to more clearly understand the message or even just enjoy the meme. The reader will be able to understand the content as a result.